Evaluation of the Mental Workload of PSIT Employees at SIT XYZ Institutions - Teguh Aprianto; Agus Rahmat Hermawanto; Rimba Krisnha Sukma Dewi; Angling Sugiatna; Abdul Fatah (Universitas Insan Cendekia Mandiri, 2023)
The results of the Subjective Self Rating Test (SSRT) questionnaire in the Information and Technology System Development section showed that workers experienced symptoms of severe head, fatigue, drowsiness, yawning, forgetfulness, awkwardness and stiffness. This indicates a problematic workload. This study aims to see the level of mental workload of each staff. The method in this study used NASA-TLX. Based on calculations, it was found that staff 4 has a mental workload score of 84.67 which means it is very high, staff 6 has a mental workload score of 27.33 with a low category, and for other staff has a high mental workload, which is a range of values from 66 to 74.67.